Exploring the potential of Lacticaseibacillus paracasei M11 on antidiabetic, anti‐inflammatory, and ACE inhibitory effects of fermented dromedary camel milk (Camelus dromedaries) and the release of antidiabetic and anti‐hypertensive peptides. Issue 12 (7th October 2022) - Shukla, Pratik; Sakure, Amar; Pipaliya, Rinkal; Basaiawmoit, Bethsheba; Maurya, Ruchika; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Hati, Subrota
Abstract: The goal of this investigation was to find antidiabetic peptides and inhibit angiotensin converting enzyme (ACE) in Lacticaseibacillus paracasei (M11) fermented dromedary camel milk ( Camelus dromedaries ). According to the findings, the rate of antidiabetic activity increased along with the incubation periods and reached its peak after 48 hr of fermentation. The inhibitions of α‐amylase, α‐glucosidase, and lipase were 80.75, 59.62, and 65.46%, respectively. The inhibitory activity of ACE was 78.33%, and the proteolytic activity was 8.90 mg/mL. M11 at 0.25 mg/mL effectively suppressed LPS‐induced pro‐inflammatory cytokines and their mediators such as NO, TNF‐α, IL‐6, and IL‐1β in RAW 264.7 cells. The rate of inoculum in the optimization phase was 1.5–2.5%, and the greatest proteolytic activity was observed after 48 hr of fermentation. The investigation of the above property in the ultrafiltered fermented milk exhibited the highest antidiabetic and ACE inhibition activities in the 3 kDa than 10 kDa fractions. The molecular weight was determined employing SDS‐PAGE, and the six‐peptide sequences were identified using 2D gel electrophoresis. Due to its high proteolytic activity, the L. paracasei strain has been reported to be useful in the production of ACE‐inhibitory and antidiabetic peptides. Amino acid sequences such from ɑ1, ɑ2, and β‐caseins have been identified within fermented camel milk by searching on online databases, including BIOPEP (for antidiabetic peptides) and AHTPDB (for hypertension peptides) to validate the antidiabetic and ACE‐inhibitory actions of several peptides. Practical applications: The study aims to identify antidiabetic peptides and inhibit ACE in dromedary camel milk fermented with Lacticaseibacillus paracasei M11. Maximum antidiabetic and ACE‐inhibitory actions of the fermented camel milk were observed in 3 kDa permeate fractions. Fermented camel milk significantly reduced the excessive TNF‐α, IL‐6, and IL‐1β production in LPS‐activated RAW 264.7 cells. RP‐LC/MS was used to identify 6 bioactive peptides from dromedary fermented camel milk. This fermented camel milk could be used for the management of hypertension and diabetic related problems. Abstract : Antidiabetic and ACE inhibitory peptides from fermented dromedary camel milk (Indian Breed) with Lacticaseibacillus paracasei (M11) and anti‐inflammatory property in RAW 264.7 cells.